The contributions of filaments and cross‐bridges to sarcomere compliance in skeletal muscle. (1st September 2014) - Brunello, Elisabetta; Caremani, Marco; Melli, Luca; Linari, Marco; Fernandez‐Martinez, Manuel; Narayanan, Theyencheri; Irving, Malcolm; Piazzesi, Gabriella; Lombardi, Vincenzo; Reconditi, Massimo
Abstract : Key points: Muscle contraction is driven at the molecular level by a structural working stroke in the head domain of the myosin cross‐bridge linking the thick and thin filaments. Crystallographic models suggest that the working stroke corresponds to a relative movement of 11 nm between the attachments of the head domain to the thin and thick filaments. The molecular mechanism of force generation depends on the relationship between cross‐bridge force and movement, which is determined by cross‐bridge and filament compliances. Here we measured the compliance of the cross‐bridges and of the thin and thick filaments by combining mechanical and X‐ray diffraction experiments. The results show that cross‐bridge compliance is relatively low and fully accounted for by the elasticity of the myosin head, suggesting that the myosin cross‐bridge generates isometric force by a small sub‐step of the 11 nm stroke that drives filament sliding at low load. Abstract: Force generation in the muscle sarcomere is driven by the head domain of the myosin molecule extending from the thick filament to form cross‐bridges with the actin‐containing thin filament. Following attachment, a structural working stroke in the head pulls the thin filament towards the centre of the sarcomere, producing, under unloaded conditions, a filament sliding of ∼11 nm. The mechanism of force generation by the myosin head depends on the relationship between cross‐bridge force and movement, which is determined by compliances of the cross‐bridge ( C cb ) and filaments. By measuring the force dependence of the spacing of the high‐order myosin‐ and actin‐based X‐ray reflections from sartorius muscles of Rana esculenta we find a combined filament compliance ( C f ) of 13.1 ± 1.2 nm MPa −1, close to recent estimates from single fibre mechanics (12.8 ± 0.5 nm MPa −1 ). C cb calculated using these estimates is 0.37 ± 0.12 nm pN −1, a value fully accounted for by the compliance of the myosin head domain, 0.38 ± 0.06 nm pN −1, obtained from the intensity changes of the 14.5 nm myosin‐based X‐ray reflection in response to 3 kHz oscillations imposed on single muscle fibres in rigor. Thus, a significant contribution to C cb from the myosin tail that joins the head to the thick filament is excluded. The low C cb value indicates that the myosin head generates isometric force by a small sub‐step of the 11 nm stroke that drives filament sliding at low load. The implications of these results for the mechanism of force generation by myosins have general relevance for cardiac and non‐muscle myosins as well as for skeletal muscle.